GAPH Survey Forms 160-202 March 1981 - Smith, Bartholemew (South Georgia Area Planning and Development Commission, 1981)
1. Middle Section of County, Brooks County, Georgia 2. Middle Section of County, Brooks County, Georgia 3. Middle Section of County, Brooks County, Georgia 4. Middle Section of County, Brooks County, Georgia 5. Middle Section of County, Brooks County, Georgia 6. Middle Section of County, Brooks County, Georgia 7. Middle Section of County, Brooks County, Georgia 8. GA Highway 369 Section of County, Brooks County, Georgia 9. GA Highway 369 Section of County, Brooks County, Georgia 10. Dixie, Brooks County, Georgia
Keywords: Lowndes County Historical Society (Lowndes County, Ga.); Real Property Surveys; Brooks County (Ga.); Historic Buildings